Histology of myopic posterior scleral staphylomas - Jonas, Jost B.; Ohno-Matsui, Kyoko; Holbach, Leonard; Panda-Jonas, Songhomitra (Acta Ophthalmologica, 2020)
Purpose: Since histomorphometric descriptions of posterior scleral staphylomas, although forming a major part of myopic maculopathy, have been scarce so far, we histomorphometrically examined scleral staphylomas in enucleated human eyes. Methods: Using light microscopy, we histomorphometrically examined sagittal histological sections of human globes enucleated due to malignant choroidal melanomas or secondary angle-closure glaucoma. Results: Out of 246 globes included into the study, posterior scleral staphylomas were detected in 10 eyes (mean length: 31.4 ± 3.0 mm; range: 28.0–37.0 mm). In the staphylomatous region in the study group as compared with the corresponding region of a control group adjusted for age and axial length, scleral thickness was significantly lower (109 ± 25 µm versus 319 ± 161 µm; p = 0.001). The study group in the staphylomatous region as compared to the highly myopic control group in the corresponding region did not differ significantly in retinal pigment epithelium (RPE) cell density (19.6 ± 4.9 cells/300 µm versus 21.1 ± 5.7 cells/300 µm; p = 0.84) and RPE height (8.2 ± 2.8 µm versus 6.1 ± 2.5 µm; p = 0.13), Bruch’s membrane (BM) thickness (3.5 ± 1.3 µm versus 4.2 ± 2.3 µm; p = 0.40) and choriocapillaris thickness (5.3 ± 2.8 µm versus 4.4 ± 2.8 µm; p = 0.49) and density (164 ± 99 µm versus 226 ± 38 µm; p = 0.13). All staphylomatous regions showed a localized BM defect. Conclusions: Marked scleral thinning and spatially correlated BM defects histologically characterized myopic scleral staphylomas, while thickness and density of the choriocapillaris and RPE and BM thickness did not differ significantly between staphylomatous versus non-staphylomatous eyes in the respective regions. These findings support the notion that a locally reduced scleral resistance against a backward pushing BM led to a local scleral outpouching. The outpouching-associated increase in curvature length may stretch BM with the sequel of a localized BM rupture.
CRIS-Team Scopus Importer:2020-03-31
Keywords: Bruch’s membrane; choriocapillaris; myopia; myopic maculopathy; scleral staphyloma

Management of the Anophthalmic Socket - Heindl, Ludwig M.; Modugno, Alessandra; Holbach, Leonard; Hartong, Dyonne T. (Oculoplastic, Lacrimal and Orbital Surgery. The ESOPRS Textbook: Volume 2, 2024)
The rehabilitation with prosthetic eyes is decisive after removal of an eye, since the eyes and the periocular region are crucial for interpersonal communication. Integrated care provided by a multidisciplinary team including ocularists and ophthalmologists is recommended for these patients. Clinical socket evaluation should focus on the dry anophthalmic socket syndrome (DASS), chronic socket infection, socket cysts, socket granulomas, and socket melanosis. For contracted sockets, a non-surgical compressor treatment should be applied as first-line therapy to form stable fornices and allow adequate prosthesis fitting.
CRIS-Team Scopus Importer:2024-10-18

Peripapillary border tissue of the choroid and peripapillary scleral flange in human eyes - Jonas, Rahul A.; Holbach, Leonard (Acta Ophthalmologica, 2019)
Purpose: To assess dimensions and associations of the peripapillary border tissue of the choroid (PBT-C) and peripapillary scleral flange (PBT-S). Methods: The histomorphometric investigation included histological sections of enucleated eyes of Caucasian patients. Using light microscopy, the PBT dimensions were measured. Results: The study included 85 eyes (85 patients) with an age of 62.0 years (14.1 years) (mean (SD)) (range:37–87 years) and mean axial length of 26.7 mm (3.5 mm) (range:21.0–37.0 mm). Thicker PBT-C thickness (mean: 68.8 μm (35.7 μm)) was associated with shorter axial length (p < 0.001; standardized regression coefficient beta: −0.50), and longer PBT-C length (mean: 531 μm (802 μm)) was correlated with longer axial length (p < 0.001;beta:0.66). PBT-C cross-sectional area (mean 17 050 μm2 (10 420 μm2)) was not significantly associated with axial length (p = 0.37). Decreasing with longer axial length (p < 0.001;beta:0.64), the angle between PBT-C and Bruch's membrane was approximately 90° in non-highly myopic eyes without overhanging Bruch's membrane (BM), it ranged between 100° and 180° in eyes with BM overhanging into the intrapapillary region, and it was close to 0° in eyes with parapapillary gamma zone. Thicker thickness of PBT-S (mean:83 μm (21 μm)) was correlated with presence of glaucoma (p = 0.02). Optic nerve pia mater thickness (mean:109 μm (44 μm)) increased with glaucoma presence (p = 0.046;beta:0.31) but not with axial length (p = 0.34). Conclusions: Peripapillary border tissue of the choroid (PBT-C) and PBT-S as continuation of the optic nerve pia mater are distinct structures, with PBT-C remodelling during myopic axial elongation and PBT-S being mostly independent of axial elongation. PBT-C and PBT-S may be of importance for the optic nerve head biomechanics and PBT-C for separation of the choroidal space from the intrapapillary compartment.
CRIS-Team Scopus Importer:2019-08-27
Keywords: axial length; Bruch's membrane; choroid; histomorphometry; lamina cribrosa; myopia; parapapillary beta zone; parapapillary gamma zone; peripapillary border tissue; peripapillary scleral flange

Retinal Pigment Epithelium Cell Density and Bruch’s Membrane Thickness in Secondary versus Primary High Myopia and Emmetropia - Jonas, Jost B.; Li, Dong; Holbach, Leonard; Panda-Jonas, Songhomitra (Scientific Reports, 2020)
To assess differences between secondary high myopia (SHM) due to congenital glaucoma and primary high myopia (PHM) and non-highly myopic eyes (NHM) in the relationships between axial length and Bruch’s membrane (BM) thickness and retinal pigment epithelium (RPE) density. The histomorphometric study included human globes enucleated for reasons such as malignant uveal melanoma, end-stage painful secondary angle-closure glaucoma and congenital glaucoma. BM thickness and RPE cell density were measured upon light microscopy. The investigation included 122 eyes (mean axial length: 26.7 ± 3.7 mm; range: 20.0–37.0 mm): 7 eyes with SHM (axial length: 33.7 ± 2.1 mm; range: 31.0–37.0 mm), 56 eyes with PHM (mean axial length: 29.1 ± 2.4 mm; range: 26.0–36.0 mm) and 59 eyes in the NHM-group (axial length: 23.5 ± 1.3 mm; range: 20.0–25.5 mm). In the SHM group, longer axial length was associated with lower RPE cell density at the posterior pole (standardized regression coefficient beta: 0.92; non- standardized regression coefficient B: −2.76; 95% confidence interval (CI): −4.41, −1.10;P = 0.01), at the midpoint posterior pole/equator (beta: −0.87; B: −3.60; 95% CI: −6.48, −0.73;P = 0.03), and at the equator (beta: −0.88; B: −0.95; 95% CI: −1.68, −0.23; P = 0.02), but not at the ora serrata (P = 0.88). In the PHM-group and NHM group, RPE cell density at the posterior pole (P = 0.08) and ora serrata (P = 0.88) was statistically independent of axial length, while at the midpoint posterior pole/equator (P = 0.01) and equator (P < 0.001), RPE cell density decreased with longer axis. BM thickness in the SHM group decreased with longer axial length at the posterior pole (beta: −0.93;B: −0.29; 95% CI: −0.39, −0.14; P = 0.003), midpoint posterior pole/equator (beta: −0.79; B: −0.22; 95% CI: −0.42, −0.02; P = 0.035) and equator (beta: −0.84; B: −0.21; 95% CI: −0.37, −0.06; P = 0.017), while in the PHM-group and NHM-group, BM thickness at any ocular region was not statistically significantly correlated with axial length (all P > 0.05). In the SHM-group, but not in the PHM-group or NHM-group (P = 0.98), lower BM thickness was associated with lower RPE cell density (beta: 0.93; B: 0.09; 95% CI: 0.04, 0.14; P = 0.007), while in the eyes without congenital glaucoma the relationship was not statistically significant. In SHM in contrast to PHM, BM thickness and RPE cell density decrease in a parallel manner with longer axial length. The findings fit with the notion of BM being a primary driver in the process of axial elongation in PHM as compared to SHM.
CRIS-Team Scopus Importer:2020-03-31